2014
DOI: 10.1177/1934578x1400900237
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Constituents and Synergism Effect of the Essential Oils from Cymbopogon citratus and Alpinia galanga

Abstract: From the fresh leaf sheathes of lemongrass (Cymbopogon citratus) and rhizomes of galanga (Alpinia galanga) light yellow and colorless oils, respectively, were obtained by hydrodistillation and microwave assisted extraction (MAE) in yields of 0.24% and 0.03%, and 0.11% and trace (w/w), respectively. By GC/MS analysis, five major constituents were identified in lemongrass oil, E-citral, Z-citral, β-myrcene, selina-6-en-4-ol, and cis-ocimene, and five in galanga oil, 1,8-cineole, phenol 4-(2-propenyl)-acetate, dl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
(15 reference statements)
4
15
0
Order By: Relevance
“…nepeta, against S. aureus ATCC 25923. These results corroborate several other studies that reported additivity or moderate synergy between EOs …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…nepeta, against S. aureus ATCC 25923. These results corroborate several other studies that reported additivity or moderate synergy between EOs …”
Section: Resultssupporting
confidence: 92%
“…Once the MIC was established, the assay was redone using a narrower range adjusted appropriately. Briefly, for the EOs with an initial MIC of 10 mg/ml the final concentrations tested were: 6, 8, 10, 12, 15, 18 mg/ml; for those with an initial MIC of 20 mg/ml, were: 15, 20, 25, 30, 35 mg/ml; and finally the EOs with an initial MIC of 40 mg/ml were tested again at the concentrations of: 25,30,35,40,45, 50, 60, 70 mg/ml. Fresh colonies were picked from an overnight culture and suspended in MHB.…”
Section: Mic and Mbc Determinationmentioning
confidence: 99%
“…The antifungal effects of lemongrass in several formulations (e.g., citral, vapor phase, essential oil, or hydro-alcoholic extracts) are well-established, and the present data corroborates the literature (Abe et al, 2003 ; Silva Cde et al, 2008 ; Irkin and Korukluoglu, 2009 ; Korenblum et al, 2013 ; Amornvit et al, 2014 ; Tadtong et al, 2014 ). Considering that most Candida cells in the oral cavity are associated with biofilms, which differ substantially from planktonic cells due to their higher antifungal resistance (Ramage et al, 2014 ), investigating the behavior of cells organized in biofilms when they are exposed to LGE is of the utmost importance.…”
Section: Discussionsupporting
confidence: 90%
“…In the process of developing new pharmacologically active compounds, plants used in folk medicine represent a rational approach to the quest for drugs (Ahmad and Beg, 2001 ; Duarte et al, 2005 ; Rios and Recio, 2005 ; Vieira et al, 2014 ). Among these plants, Cymbopogon citratus , an herb known around the world as lemongrass, has been reported to exert potent inhibitory effects against Candida species (Abe et al, 2003 ; Silva Cde et al, 2008 ; Irkin and Korukluoglu, 2009 ; Amornvit et al, 2014 ; Tadtong et al, 2014 ). Thus, the application of lemongrass as an effective and easily available antifungal agent could be considered an alternative approach to reducing C. albicans biofilms on denture surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation